Teori-Teori Hubungan Hukum Agama Dengan Hukum Negara - Al Ikhlas; Desi Yusdian; Murniyetti Murniyetti; Nurjanah Nurjanah; Sulaiman Sulaiman (Jurnal Kawakib, 2022)
The formation of national law which is the basis for realizing justice in Indonesia has gone through a long process. Starting from the entry of Islam into Indonesia and is still ongoing now. In the formation of the national law, there are at least four theories that explain how the struggle for legal sources that have been integrated with Indonesian society has crystallized into the main guideline in regulating the lives of Indonesian people. The sources of law are Religious Law, Customary Law, and Dutch Law. Combining these three sources of law to become national law is not simple. So that clashes often occur which results in the birth of various conflicts in the community. In particular, when the Dutch Colonial tried to apply their laws in Indonesia, they set rules according to their interests in order to strengthen their grip on the colonized country. So to explain how the process of forming national law, there are several theories that can explain it, namely: Receptie in Complex, Receptie, Receptie a Contrario, and Eclecticism. This research is in the form of qualitative which tends to be analytical and descriptive. Data were collected from various relevant literature and then analyzed using interactive methods. Thus, the findings of this study are that the theory of Receptie in Complex, Receptie, Receptie a Contrario, and Eclecticism explains that national law and religious law have a strong relationship. So national law and religious law will always be united in their principles because the majority of Indonesian people are Muslims.